A Risk Assessment Framework of Photovoltaic Poverty Alleviation Projects under EPC Mode in China. (5th August 2022) - Chu, Han; Xu, Minjia; Wu, Yunna
Abstract : Due to the characteristics of poverty alleviation and cleanness, the photovoltaic poverty alleviation project (PPAP) plays an important role in consolidating the link between poverty alleviation and "rural revitalization" in China, which has attracted the attention of all sectors of society. In practice, EPC (engineering, procurement, and construction) mode is widely used in PPAP, which brings considerable benefits, but also has many risks. To ensure the successful development of the project, it is necessary to carry out risk assessment when selecting the scheme. However, this complex multi-attribute decision-making problem can be improved. First, the risk of PPAP is lack of targeted research; second, the uncertainty in the evaluation process has not been fully solved; third, the method of sorting is unreasonable. To solve these problems, this study establishes the risk assessment framework of PPAP. Firstly, a comprehensive index system suitable for PPAP risk assessment is established, including 5 first-level indexes and 22 second-level indexes. Then, the ANP method based on fuzzy environment is used to determine the weight. Finally, the cloud model and PROMETHEE are combined to select a higher priority solution. Case study and sensitivity analysis prove the robustness and feasibility of the framework. This study puts forward the corresponding risk response measures, to provide reference for the future practice of risk prevention and control.